Use of morphometric measurement for estimation of AI timing of Hanwoo heifer (Korean native cattle) - Inchul Choi; Donghan Shin; Shinyong Jung; Seongwon Seo (The Korean Society of Animal Reproduction and Biotechnology, 2016)
The aim of the present study was to evaluate and estimate timing of artificial insemination (AI) in Hanwoo heifer (Korean native cattle) that is the most popular breed of beef cattle in Korea. To determine changes in body weight of heifers around AI, body weight were measured at different stages either before or after AI. We found that daily body weight gain was higher in the pregnant cows after AI. We also investigate correlation between body mass measured by shoulder height and body length, and conception rates, used (body length+ height)2 instead of height2 for body mass index (BMI), and found that relatively more BMI heifers (>55) showed higher conception rates. Finally, we estimated body weight by measuring should height (SH), heart girth (HG), and body length (BL); BW=3.93372*HG-2.90985*SH-0.021*BL. In addition, we observed that HG is most closely correlated with BW; y(BW) = 1.77355*x(HG), R2 = 0.98881. In summary, we can determine the best timing of AI using body measurement and its application including BMI.